The Effect of Liquidity, Leverage, and Company Growth on Going Concern Audit Opinion in Retail Sub-sector Companies - Rika Centani Sukma; Januar Eko Prasetio (AIBPM Publisher, 2024)
This study aims to provide empirical evidence regarding the factors that can affect going concern audit opinion on retail sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The background of this study is the importance of going concern audit opinion which is one of the early warnings for the company's business continuity, especially in the retail sector which is vulnerable to economic fluctuations. A quantitative approach was used with a population of retail sub-sector companies listed on the IDX during the period. With the purposive sampling method, 72 samples were selected. Liquidity is measured by current ratio, leverage by debt-to-equity ratio, and company growth by sales growth. Logistic regression analysis was used to test the proposed hypothesis. The results showed that leverage has a significant effect on going concern audit opinion, while liquidity and company growth have no significant effect. These findings provide new insights into understanding the dynamics of going concern audit opinion in the retail sub-sector, as well as providing a basis for further research in exploring other factors that may affect audit opinion. Future research is recommended to add non-financial variables and expand sector coverage to strengthen the generalizability of the results.